Numerical simulation of jet impingement relaminarization using nonlinear eddy viscosity turbulence models - Mongkol Kaewbumrung; Chalermpol Plengsa-Ard (Engineering Applications of Computational Fluid Mechanics, 2023)
This numerical study investigated a single air jet impingement at a constant temperature. Different RANS turbulence models, namely the v2-f model and four Reynolds stress turbulence models (the linear pressure-strain model, the quadratic pressure-strain model, the stress-omega model and the stress-BSL model) were employed to simulate and compare the numerical results with other published measurement data. Here, we show that the v2-f model has better numerical precision in simulating the local Nusselt number and velocity profiles and is in good agreement with a variety of Reynold numbers. These findings can assist scientists or engineers to improve mathematical turbulence modeling and industrial equipment for further development and to enable innovation.